2018
DOI: 10.1016/j.cell.2018.08.062
|View full text |Cite
|
Sign up to set email alerts
|

NONO Detects the Nuclear HIV Capsid to Promote cGAS-Mediated Innate Immune Activation

Abstract: Detection of viruses by innate immune sensors induces protective antiviral immunity. The viral DNA sensor cyclic GMP-AMP synthase (cGAS) is necessary for detection of HIV by human dendritic cells and macrophages. However, synthesis of HIV DNA during infection is not sufficient for immune activation. The capsid protein, which associates with viral DNA, has a pivotal role in enabling cGAS-mediated immune activation. We now find that NONO is an essential sensor of the HIV capsid in the nucleus. NONO protein direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
198
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(209 citation statements)
references
References 58 publications
10
198
1
Order By: Relevance
“…This is similar to the response to cytosolic DNA, where cGAS produces the mammalian cyclic di-nucleotide cGAMP (cyclic GMP-AMP), which also binds and activates STING. nucleus, have recently been discovered [5,6], and, as further demonstrated by Kaufmann and colleagues [1], cGAS function is not always restricted to DNA sensing and cGAMP production. Indeed, the way in which STING is activated by cGAS or other regulators appears to have consequences for its mode of signalling.…”
Section: Leonie Unterholznermentioning
confidence: 98%
“…This is similar to the response to cytosolic DNA, where cGAS produces the mammalian cyclic di-nucleotide cGAMP (cyclic GMP-AMP), which also binds and activates STING. nucleus, have recently been discovered [5,6], and, as further demonstrated by Kaufmann and colleagues [1], cGAS function is not always restricted to DNA sensing and cGAMP production. Indeed, the way in which STING is activated by cGAS or other regulators appears to have consequences for its mode of signalling.…”
Section: Leonie Unterholznermentioning
confidence: 98%
“…Vaccines are an important tool to prevent spread of infection, but for diseases like malaria and human immunodeficiency virus (HIV), the development of vaccines has been challenging. [27,28] Studies in these and other challenging infectious diseases indicate advantageous correlations between innate immune states and vaccine efficacy, motivating immune engineered biomaterials that exploit innate immunity to enhance vaccine efficacy. Vaccines that prevent malaria transmission have been challenging to produce because the adaptive response and production of parasitetargeting antibodies is insufficient.…”
Section: Immunity Is Ill-prepared To Eliminate Some Infectious Diseasesmentioning
confidence: 99%
“…HIV-1 capsids prevent both innate immune sensing of viral cDNA by the cGAS-STING [cyclic guanosine monophosphate-adenosine monophosphate (GMP-AMP) synthase and stimulator of IFN genes] pathway as well as cDNA degradation and sensing by endogenous DNase enzymes such as TREX1 (three prime repair exonuclease 1) [48,49]. It was recently reported that HIV-2 capsid binds more strongly than HIV-1 to the non-POU domain-containing octamer-binding protein (NONO) protein in the nucleus, promoting DNA sensing by cGAS and stimulating a potent IFN response [52]. Capsid structures are highly conserved among retroviruses, and mutations in their sequence may either reduce viral infectivity or increase the susceptibility of the virus to host immune responses [50,51].…”
Section: The Importance Of Gagmentioning
confidence: 99%
“…In contrast to HIV-1, HIV-2 is able to replicate in dendritic cells and stimulates innate immune sensing via its capsid in a cyclophilin A-dependent manner [35]. The capsid residues involved in NONO binding are highly conserved in primate lentiviruses [52]. It was recently reported that HIV-2 capsid binds more strongly than HIV-1 to the non-POU domain-containing octamer-binding protein (NONO) protein in the nucleus, promoting DNA sensing by cGAS and stimulating a potent IFN response [52].…”
Section: The Importance Of Gagmentioning
confidence: 99%
See 1 more Smart Citation